Mild cold stress specifically disturbs clustering movement of DFCs and sequential organ left-right patterning in zebrafish - Liu, Min; Zou, Xinyu; Fu, Mao; Bai, Xinping; Zhao, Yongyan; Chen, Xin; Wang, Xiaoyu; Wang, Peijian; Huang, Sizhou (Frontiers in Cell and Developmental Biology, 2022)
In poikilothermic animals, the distinct acclimatization ability of different organs has been previously addressed, while the tissue-specific role of cold stress in early development is largely unknown. In this study, we discovered that despite its role in delaying embryonic development, mild cold stress (22°C) does not disturb multiple-organ progenitor specification, but does give rise to organ left-right (LR) patterning defects. Regarding the mechanism, the data showed that mild cold stress downregulated the expression of cell-adhesion genes cdh1 and cdh2 during gastrulation, especially in dorsal forerunner cells (DFCs), which partially disturbed the clustering movement of DFCs, Kupffer’s vesicle (KV) morphogenesis, and ciliogenesis. As a result, the defects of KV/cilia disrupted asymmetric nodal signaling and subsequent heart and liver LR patterning. In conclusion, our data novelly identified that, in early development, DFCs are more sensitive to mild cold stress, and mild cold stress repressed the expression of cell adhesion-related gene cdh1 and cdh2. This role partially disturbed the clustering movement of DFCs, which resulted in defective KV/cilia development and sequential organ LR patterning defects.